Study demands, study resources and the role of personality characteristics in predicting the engagement of fist-year university students - Cilliers, J.R.; Mostert, K.; Nel, J.A. (South African Journal of Higher Education, 2018)
The main objectives of the present study were to 1) determine significant demands and resources associated with student engagement; and 2) establish the incremental contribution of personality in predicting the engagement of first-year university students. A stratified sample of 512 first-year university students was used. The results showed that pace and amount of work, and cognitive demands had a significant and negative correlation with engagement. However, only cognitive demands was found to be a significant predictor of engagement in the second and third step of the regression analysis and became insignificant in the fourth and final step of the analysis when personality characteristics were added. All the resources had significant and positive correlations with engagement, but only support from lecturers and opportunities for growth and development were found significant predictors of engagement. In the fourth and final step of the regression analysis, the only significant resource was opportunities for growth and development. All the personality dimensions showed a significant relationship with engagement. However, in the final step of the regression analysis, only achievement orientation (a facet of conscientiousness) turned out to be a significant predictor of student engagement. The model in which personality characteristics were entered added an additional 11% of the variance explained in engagement, which indicates the incremental contribution to student engagement.